Estudo da doença residual mínima e sua relação com critérios de estratificação de risco de leucemia linfóide aguda na infância - Salina, Thais Ditolvo Da Costa (2015)
Acute lymphoblastic leukemia (ALL) is the most common childhood cancer, descendant from the clonal expansion of immature lymphoid precursors from both B or T lines. The ALL accounts for about 75% of cases of leukemia in children younger than 15 years and only 20% of the adult cases. The current increase in survival of ALL in children is due to advances in diagnosis, establishment of prognostic factors and the use of treatments accoding to risk groups. The relapse risk stratification may vary by therapy protocol, but in general, are important prognostic factors: age and white blood cell count at diagnosis, immunophenotype, presence of lymphoblasts in the central nervous system, cytogenetic analysis of chromosomal abnormalities and evidence of minimal residual disease (MRD) in children in clinical and morphological remission. Currently the best predictor of prognosis in acute lymphoid leukemia in childhood is monitoring the MRD. Based on their findings, it is possible to optimize chemotherapy while minimizing toxicity and decreasing risk of relapse. In this context, this study aimed to evaluate the MRD application in relapse risk stratification in children with B ALL during induction therapy and compare with clinical and laboratorial criteria for relapse risk stratification. The study included 1-17 years old patients recently diagnosed with B ALL in chemotherapy induction phase, using a convenience sample from January 2014 to January 2015. The MRD was detected by flow cytometry (FC-MRD) based on identifying anomalous phenotypes as residual disease markers. Results demonstrated correlation between manual blasts count and CF-MRD samples with more than 5% blasts D8 (r = 0.54; p = 0.0008) and D15 (r = 0.91; p <0.0001). It was observed that the CF-MRD research in the early stages of treatment recognized groups of patients who suffer risk of re-stratification later in GBTLI2009 protocol. In the case of high risk patients the results initially suggest that levels of CF-MRD ≥1% in early D8 may identify patients who will be re-laminated in slow responders at D15 (p = 0.0097). The CF-MRD search on D35 was able to detect a portion of patients with positive MRD (37.9%) despite complete morphological remission, and can become an alternative way for locations where the PCR-MRD survey is not available. These data shows the importance of including the outcome of MRD research in risk stratification during induction therapy.